A community challenge for a pancancer drug mechanism of action inference from perturbational profile data - Douglass, Eugene F.; Allaway, Robert J.; Szalai, Bence; Wang, Wenyu; Tian, Tingzhong; Fernández-Torras, Adrià; Realubit, Ron; Karan, Charles; Zheng, Shuyu; Pessia, Alberto; Tanoli, Ziaurrehman; Jafari, Mohieddin; et al. (Cell reports. Medicine, 2022)
The Columbia Cancer Target Discovery and Development (CTD2) Center is developing PANACEA, a resource comprising dose-responses and RNA sequencing (RNA-seq) profiles of 25 cell lines perturbed with ∼400 clinical oncology drugs, to study a tumor-specific drug mechanism of action. Here, this resource serves as the basis for a DREAM Challenge assessing the accuracy and sensitivity of computational algorithms for de novo drug polypharmacology predictions. Dose-response and perturbational profiles for 32 kinase inhibitors are provided to 21 teams who are blind to the identity of the compounds. The teams are asked to predict high-affinity binding targets of each compound among ∼1,300 targets cataloged in DrugBank. The best performing methods leverage gene expression profile similarity analysis as well as deep-learning methodologies trained on individual datasets. This study lays the foundation for future integrative analyses of pharmacogenomic data, reconciliation of polypharmacology effects in different tumor contexts, and insights into network-based assessments of drug mechanisms of action.
Gesehen am 20.12.2022